Gastrointestinal foreign bodies in Dogs and Cats: (2018–2020) 32 Cases - Cafer Tayer İşler; Ömer Kırgız; Mehmet Zeki Yılmaz Deveci; İbrahim Alakuş; Halil Alakuş; Ziya Yurtal; Muhammed Enes Altuğ (Revista Científica, 2022)
Gastrointestinal foreign bodies (GFB) in cats and dogs are among the life-threatening surgical diseases that require invasive surgery. This study aimed to evaluate the cases of GFB in 32 cats and dogs diagnosed and treated in Hatay Mustafa Kemal University Veterinary Health Practice and Research Hospital. Information regarding the type, breed, age, sex, clinical symptoms, characteristics of foreign bodies (FB), localization, prognosis, type of treatment administered, and conditions determined in postoperative controls was collected. The cases were aged between 1 and 7 years and adult animals were also included. The rate of FB incident was the same in male and female cats, whereas male dogs had a higher rate of FB incident. Strings/ropes and metallic objects were the most common foreign objects found in animals. Early diagnosis and treatment were important in preventing complications in the cases, FB was usually found in the stomach, and vomiting was the most common clinical symptom. Further, surgical intervention (gastrostomy/enterotomy) was the most common treatment method with a rate of 53.13 % for treating FB in the gastrointestinal system that yielded successful results. Thus, to avoid complications and for a good prognosis, owners must be conscious and seek for diagnosis and treatment as soon as they notice the incidence of swallowing a FB, so as to ensure early diagnosis and treatment.